2000
DOI: 10.1098/rstb.2000.0733
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning through the combination of primitives

Abstract: In this paper we discuss a new perspective on how the central nervous system (CNS) represents and solves some of the most fundamental computational problems of motor control. In particular, we consider the task of transforming a planned limb movement into an adequate set of motor commands. To carry out this task the CNS must solve a complex inverse dynamic problem. This problem involves the transformation from a desired motion to the forces that are needed to drive the limb. The inverse dynamic problem is a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(194 citation statements)
references
References 59 publications
(80 reference statements)
3
189
0
2
Order By: Relevance
“…Bizzi et al (1991), Mussa-Ivaldi et al (1994), and more recently, Lemay et al (2001) have shown that the simultaneous stimulation of two sites, each generating a different force field, results in the vector sum of the two fields in most instances. When the pattern of forces recorded at the ankle following co-stimulation were compared with those computed by summation of the two individual fields, Mussa-Ivaldi et al (1994) found that the "co-stimulation fields" and the "summation fields" were equivalent in more than 87% of cases. Similar results have been obtained by Tresch and Bizzi, (1999) by stimulating the spinal cord of the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Bizzi et al (1991), Mussa-Ivaldi et al (1994), and more recently, Lemay et al (2001) have shown that the simultaneous stimulation of two sites, each generating a different force field, results in the vector sum of the two fields in most instances. When the pattern of forces recorded at the ankle following co-stimulation were compared with those computed by summation of the two individual fields, Mussa-Ivaldi et al (1994) found that the "co-stimulation fields" and the "summation fields" were equivalent in more than 87% of cases. Similar results have been obtained by Tresch and Bizzi, (1999) by stimulating the spinal cord of the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Although the internal model and impedance control hypotheses were initially thought to be contradictory to one another (but see (Mussa-Ivaldi and Bizzi 2000)), recent studies suggest that they could co-exist during motor learning (Burdet, Osu. et al 2001;Franklin, Osu et al 2003).…”
Section: Dual Sliding Mode and High-gain Adaptive Control Of Hand Movmentioning
confidence: 99%
“…Then, We learn nonlinear mapping between the low dimensional manifold representation and the original high dimensional motion. The low dimensional manifold representation is motivated by force fields in the biological study of human motion [10]. The motion primitives that we are interested in are relevant to the intrinsic body configuration and irrelevant to the position and orientation of the body.…”
Section: Learning Low Dimensional Motion Manifoldmentioning
confidence: 99%
“…Biological study shows that complicated human motions are controlled by linear combination of computational motion primitives called force fields [10]. We learn a generative model with a low dimensional motion manifold representation similar to force fields of motion primitives.…”
Section: Introductionsmentioning
confidence: 99%